Analisis Penerapan Activity-Based Management (ABM) dan Pengungkapan Informasi Strategis pada PT Indofood Sukses Makmur Tbk - Paulina Merlinda; Dwi Aprillia Heriani; Enjelina Putika S; Andika Saputra; Agus Wahyudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyse PT Indofood Sukses Makmur Tbk's implementation of the Activity-Based Management (ABM) approach and the extent to which the company discloses strategic information in its fourth quarter annual report. The study focuses on cost efficiency, management of corporate activities, and transparency in disclosing information related to ownership structure, leverage, and profitability. The analysis shows that the implementation of ABM can help companies maximise value-added activities and reduce unnecessary costs. However, the disclosure of strategic information, especially related to share ownership and financing structure, is still not fully transparent to the public.